Praktik Baik Pemanfaatan Media Ajar Digital dalam Kegiatan Pembelajaran: Pengabdian - Jumiati Nur; Abdul Azis; Fitriani; Hardianto; Minzar; Rosliah; Hikmah Idris; Tria Mulya Utari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Community Service (PKM) activities in the form of socialization of the Use of Digital Teaching Media in Learning Activities at UPTD SDN 109 INPRES LEKOALA, is a relevant issue amidst current technological developments. This article aims to socialize the use of digital media based on Google Sites integrated with Canva and evaluation using Wayground to teachers at UPTD SDN 109 INPRES LEKOALA. This PKM activity was carried out collaboratively with lecturers from Muhammadiyah University of Makassar, students of the Elementary Education Masters Program at Muhammadiyah University of Makassar, and teachers of UPTD SDN 109 INPRES LEKOALA. This activity was carried out in three stages, namely the planning, implementation and reporting stages. The planning stage consists of determining the theme, conducting observations, formulating solutions and then compiling materials. The implementation stage consists of delivering material about Google Site-based digital media integrated with Canva and evaluation using Wayground. The reporting stage consists of compiling reports and publications. The results of this activity show that teachers are enthusiastic about participating in socialization activities so that teachers understand the use of digital media based on Google Sites integrated with Canva and evaluation using Wayground.